2021
DOI: 10.25259/jmsr_83_2021
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Orthopedic Trauma during COVID-19 Crisis in Saudi Arabia: Report from Level I Trauma and COVID-19 Center

Abstract: Objectives: The aim of this study was to provide the pattern of orthopedic trauma catered at our center during the lockdown to stop the spread of SARS-CoV-2 and compare it during the same period in the preceding year. Methods: A retrospective study of all trauma patients operated during partial and total lockdown during March– July 2020, was conducted at the orthopedic department of King Fahd Hospital of the University, Al-Khobar. The data collected were age, gender, reason for hospital admission, date of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The study showed no significant association between demographics of trauma cases before and during the COVID-19 pandemic, and this is logical as personal characteristics for susceptible personnel to trauma will not be affected by the trauma phase (nearly the same age and gender). Similar findings were found in the Al-Khobar study regarding age and gender differences, where the average age and adults' gender were similar before and during the COVID-19 pandemic [ 5 ]. In contrast, a study done in Pennsylvania reported significant differences in traumatized ages but not for gender [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The study showed no significant association between demographics of trauma cases before and during the COVID-19 pandemic, and this is logical as personal characteristics for susceptible personnel to trauma will not be affected by the trauma phase (nearly the same age and gender). Similar findings were found in the Al-Khobar study regarding age and gender differences, where the average age and adults' gender were similar before and during the COVID-19 pandemic [ 5 ]. In contrast, a study done in Pennsylvania reported significant differences in traumatized ages but not for gender [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
“…In Al-Khobar City, Saudi Arabia, the University Hospital found that there were 71 admissions during the quarantine compared to 110 in the previous year. The patient's number reduced by 35.4%, mainly in women and children groups [ 5 ]. The study showed no significant association between demographics of trauma cases before and during the COVID-19 pandemic, and this is logical as personal characteristics for susceptible personnel to trauma will not be affected by the trauma phase (nearly the same age and gender).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study only counted patients admitted through the emergency room and did not count admissions through the clinic for emergency procedures. The study showed a significant decrease in the length of stay from 18.9 (Standard deviation = 12,7) to 4.3 (Standard deviation = 3.5) days [ 17 ]. We believe such a decrease is related to the new policies implemented during the COVID-19 pandemic to decrease exposure to patients, staff and accommodate new admissions in overwhelming circumstances.…”
Section: Discussionmentioning
confidence: 99%